DOUBLE-VOICING IN THE MOUTH OF INDONESIAN COMEDIAN - Nirwan, Nirwan; Ramadhina, Retno; Priyoto, Priyoto (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
In Indonesian context, particularly within the entertainment sphere: TV, YouTube, TikTok many produced utterances which can be interpreted from novel analysis and semiotic point of view. Speech here indexes to all artists â€˜utterancesâ€™ which are relevant to this topic. The topic of this article is Indonesian comedy, more specifically, concerning to political and sexual jokesâ€”a kind of political and sexual sarcasm. Jokes and critiques are living together on the stage of comedy. The dialogues between the actors who were involved are usually producing double meaning and consequently it produces double understanding in audienceâ€™ mind. The data sources of this research were taken from two programs, namely TV show â€œLapor Komandanâ€ in Trans7 and YouTube show â€œin Deddy Corbusierâ€™s YouTube Channel. These data are comedy shows. The writing applies the semiotic interactional of indexicality which was developed by Michael Silverstein and Bakhtinâ€™s theory of dialogism through double voice that has been applied in the novel. The rationality is to get a better understanding on how a comedian plays creativity through the words in producing double voiceâ€”dialogical imagination. The term â€œdouble voicingâ€ was developed by a Russian philosopher to index the speech phenomenon produced by speakers. Clearly, it stated that every speech is always linked to other speech through imagination. The speech has multi linguistic meaning that can represent the specific communities, organizations, and individuals. The result shows that there are three kinds of double voice or double meaning gained from the interactional conversation, those are, the sexual jokes, political and violation jokes.